Psychometric Properties of the Gratitude Scale (GRAT) among a Sample of Students at the Faculty of Education at Hamah University (Journal of Hama University, 2026)
the research aimed to verify the psychometric properties of the Gratitude Scale (GRAT) which was developed by Watkins and others (Watkins, et al., 2003) and applied on a sample of (445) male and female students at the Faculty of Education at Hamah University, students were using a stratified random method. A descriptive analytical approach was undertaken. The following results were obtained in the research:- The results of the Exploratory Factor Analysis (EFA) showed that the scale items were saturated into three separate factors that explained (77.375) of the total variance.- The results of the hypothetical construction validity showed the presence of positive and statistically significant correlation coefficients between the items and the total score of the scale, ranging between (0.607-0.783).- The results of the categorical validity test, with reference tow extreme groups in the scale, showed a statistically significant difference between the mean scores of the upper and lower groups on all items of the scale and its total score.- The results showed the scale's reliability through Cronbach's alpha equation, with values ranging between (0.959-0.984), and through the spilt-half method using the Spearman-Brown equation, with values ranging between (0.959-0.984).The researcher suggested studying the psychometric properties of the scale on other samples of students at Hamah University, extracting criteria for interpreting its raw scores, and using it in psychological and educational researches related to gratitude variable.
Keywords: Psychometric Properties; Gratitude Scale (GRAT); Students at the Faculty of Education; Hamah University